Effect on carrot substitution on nutrition facts, Beta-Carotene, and hedonic characteristic of rabbit meat nugget - Susanti, Siti; Katherinatama, Aldia; Ayu Aryani , Dyah; Afifah, Diana Nur; Nugroho, Trilaksana; Arifan, Fahmi (Progress in Nutrition, 2023)
Background and aim: The use of rabbit meat nuggets offers several health benefits since rabbit meat has more protein than chicken meat and less fat, making it suitable for consumption by those with cardiovascular disease. Nevertheless, rabbit meat nuggets are somewhat expensive compared to chicken meat. Thus, additional ingredients are required as a substitute for rabbit meat nuggets without changing the taste or compromising the nutritional content of rabbit meat nuggets. Carrots will be used as a substitute for rabbit meat nuggets in this study due to their high fiber content and beta-carotene, which will increase the nutritional value of rabbit meat nuggets. Methods: The experimental design used in this study used a single factor of 3 treatments with 3 repetitions, namely differences in carrot substitution (0%, 20%, and 40%) in rabbit meat nuggets. The data from the chemical and physical analysis were analyzed using SPSS for windows 26.0. Results: The results showed that rabbit meat nuggets with carrot substitution were high in beta-carotene and fiber (p<0.05). The substitution of carrots up to 40% is still at the panelists’ preferred level. Conclusions: The substitution of carrots to rabbit meat nuggets improved the nutritional benefits, raising fiber and beta-carotene levels in the nuggets.